Odmeravanje kazne i generalna prevencija - Zoran Stojanović (Revija za kriminologiju i krivično pravo)
The paper deals with the question of whether it is necessary and justified for general preventive expectations to be the immediate basis for sentencing. General prevention (deterrence) should be achieved primarily if not exclusively when prescribing the punishment. The application of criminal law and punishment should demonstrate that the threat of punishment is serious. However, it is not necessary to determine what measure of punishment is needed in a specific case in order to influence others not to commit criminal acts. It is not even possible to determine exactly, but a general assessment is sufficient, i.e. the court's impression that with a measured punishment, general prevention can be achieved, both negative (traditional) and positive, which consists in expressing social condemnation for a criminal offense, strengthening moral and strengthening the obligation to respect the law. It is sufficient for the court to determine the punishment, as the law says, "taking into account" the purpose of the punishment. In particular, the paper points out the unacceptability of stricter punishment due to the expected general prevention. At the same time, the importance of the positions taken in this respect in his works by Jovan Ćirić, to whom this work is dedicated, is pointed out.